2013
DOI: 10.1002/dvdy.23907
|View full text |Cite
|
Sign up to set email alerts
|

A Technique to Increase Accessibility to Late‐Stage Chick Embryos for In Ovo Manipulations

Abstract: Background During early development avian embryos are easily accessible in ovo for transplantations and experimental perturbations. However, these qualities of the avian embryonic model rapidly wane shortly after embryonic day (E)4 when the embryo is obscured by extraembryonic membranes, making it difficult to study developmental events that occur at later stages in vivo. Results and Conclusions In this study, we describe a multistep method that involves initially windowing eggs at E3, followed by dissecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The above challenges in the ex ovo method has meant that researchers turn to the windowing method 9,10 to view embryonic chick development.…”
Section: Introductionmentioning
confidence: 99%
“…The above challenges in the ex ovo method has meant that researchers turn to the windowing method 9,10 to view embryonic chick development.…”
Section: Introductionmentioning
confidence: 99%
“…Yalcin et al [19] have utilized ex ovo chick embryo culture system to study the relationships between genetic and microenvironmental factors driving normal and malformed embryonic development [19]. During the initial days of incubation, a chick embryo, which begins as a blastoderm undergoes gastrulation, neurulation and several morphogenetic movements to form distinct cranial and trunk structures [20]. These developmental features resemble closely to human development process.…”
Section: Discussionmentioning
confidence: 99%
“…de Gennaro (1980) hypothesized that a flat‐bottomed culturing dish, that restricts the chorioallantoic membrane from completely surrounding the embryo and impeding the embryo's ability to move freely, could cause abnormalities in the morphology of the endochondral elements. However, more recently, Spurlin and Lwigale () demonstrated that preventing the chorioallantoic membrane from completely surrounding the embryo in‐ovo does not grossly affect the morphology of the embryo. Therefore, we do not believe that the changes in chorioallantoic membrane position, due to shell‐less culturing in a flat‐bottomed dish, caused the abnormalities observed in the endochondral elements.…”
Section: Discussionmentioning
confidence: 99%
“…For each of these culturing methods, there are a few different techniques. In‐ovo culturing inside a windowed egg [can be conducted with the removal of albumin (Korn and Cramer, ; Spurlin and Lwigale, ) or without this removal (Speksnijder and Ivarie, )]. Additionally, this window culturing technique can utilize wax or an adhesive tape to seal the windows in the eggshells.…”
Section: Introductionmentioning
confidence: 99%